Health education on multidrug-resistant tuberculosis prevention among tuberculosis patients - Hema Malini; Emil Huriani; Devia Putri Lenggogeni; Shinta Herlina (International Journal of Public Health Science (IJPHS), 2021)
The high incidence of multidrug-resistant tuberculosis (MDR-TB) in the community due to the lack of socialization or the provision of health education about MDR-TB. During this time, health education is only focused on tuberculosis (TB) generally. The purpose of this study was to determine the effect of health education on the behavior of MDR-TB prevention in patients with pulmonary tuberculosis in two Community Health Centers in Padang. This study design is quasi-experimental with pre and post-test groups only. The program intervention of health education was conducted for a month with lecture method and group discussion using flipchart and video as media. The sampling technique used purposive sampling were 29 patients with TB who are still in the phase of treatment. Data collection used a set of questionnaires. The data analysis in this study using statistical tests t-test. The results showed, there is a significance influence of health education on knowledge with p-value=0.000 (p≤0.05) and attitude with p-value=0.000 (p≤0.05). The result also showed that 65.5% of patients taking medication regularly. It was also that there is the effect of health education on the behavior of MDR-TB prevention in TB patients. It is expected that the providing of health education on the prevention of behavior on MDR-TB is emphasized on the motivation and self-efficacy of the patients and involvement of supervision on taking medication.